Four radars and three catchments - Lau,J; Onof,C (ETH Zurich, 2017)
The East Coast of Peninsular Malaysia is affected by severe rainfall and flooding brought on by moonsoon winds. The government allocation for structural flood control works escalated to USD 1.3 billion between 2005 and 2010. A project was commissioned by the Malaysian Government through the Division of Irrigation and Drainage (DID) in 2009 to investigate the validity of using radar rainfall data records to estimate rainfall rates. The processed radar rainfall data will be used as input into the flood-forecasting model for enhanced estimation of rainfall. The aim is to process radar rainfall data into a suitable format for input into hydrological models. A tool given the name Rainfall Analyzer and Integrator for Malaysia (RAIM) was developed to achieve this. The study required extensive comparisons that were carried out between the radar Quantitative Precipitation Estimates (QPE) and the ground based rain gauges. Seasonal specific empirical Z-R relationships were derived for four radar sites: Kluang, Kota Bharu, Kuantan and Subang radar. A two stage statistical approach was used to obtain the most appropriate Z-R relationship for each of the radar sites. Spatial rainfall estimates were then used as input into HEC-HMS models for three river basins in Johor, Pahang and Kelantan. The response of models to rain-gauge and spatial rainfall was compared. The comparisons concluded that the use of spatial rainfall, as compared to point rain-gauge data produced a better response when compared to recorded river levels.